Proceedings of the 10th Hellenic Relativity Conference on recent developments in gravity Kalithea/Chalkidiki, Greece, 30 May-2 June 2002 (World Scientific Pub. Co., 2003)
This book contains the proceedings of the 10th Hellenic Relativity Conference, held in Greece in 2002. It includes several plenary lectures given by leading experts on brane-world cosmology, radiative space-times, detection of gravitational waves, gamma-ray bursts and quantum gravity. There are a large number of contributed papers, organized into three broad subject areas: cosmology and brane gravity, mathematical relativity and astrophysical relativity, and the detection of gravitational waves